1971
DOI: 10.1111/j.1476-5381.1971.tb07162.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal injury on the kinin system in rabbit hind limb lymph

Abstract: Summary The kinin‐forming activity of hind limb lymph and of plasma has been examined in rabbits before and after thermal injury. Neither plasma nor lymph contained much active kallikrein activity but the enzyme was evident in samples treated with glass or with acid. There was little or no increase in the activity of enzyme activated by glass after thermal injury, but an increase in the activity of enzyme activated by acid regularly occurred. There were two increases in the activity of enzyme activated by aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although no effect was observed when the drugs were infused immediately after the injury, when they were infused 90 min after burning, the lymph protein was significantly reduced. Since Lewis & Wawretschek (1971) using the same technique showed that there were two phases of increase in lymph protein it is possible that it is this second phase, which corresponds to a second phase of increased vascular permeability (Sevitt, 1958;Burke & Miles, 1958) which was inhibited by the antiinflammatory agents. The fact that neither hydrocortisone nor indomethacin affected the increase in lymph /3-glucuronidase activity is consistent with this view, since it has been shown (Lewis, 1969) that /3-glucuronidase leaks into the lymph after injury not from the injured cells but from the plasma as a result of the initial increase in vascular permneability.…”
Section: Discussionmentioning
confidence: 99%
“…Although no effect was observed when the drugs were infused immediately after the injury, when they were infused 90 min after burning, the lymph protein was significantly reduced. Since Lewis & Wawretschek (1971) using the same technique showed that there were two phases of increase in lymph protein it is possible that it is this second phase, which corresponds to a second phase of increased vascular permeability (Sevitt, 1958;Burke & Miles, 1958) which was inhibited by the antiinflammatory agents. The fact that neither hydrocortisone nor indomethacin affected the increase in lymph /3-glucuronidase activity is consistent with this view, since it has been shown (Lewis, 1969) that /3-glucuronidase leaks into the lymph after injury not from the injured cells but from the plasma as a result of the initial increase in vascular permneability.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lewis & Wawratschek (1971), there is, after thermal injury, a pronounced increase in the lymph of an inactive form of kallikrein which can be activated by acid treatment (but not by contact with a glass surface). According to these authors, increase in vascular permeability leads to the passage of prekallikrein from the plasma into the interstitial space of the injured area.…”
Section: Introductionmentioning
confidence: 99%